Expression of LEF1 is an independent prognostic factor for patients with oral squamous cell carcinoma - Min-Cheng Su (Journal of the Formosan Medical Association, 2014)
Lymphoid-enhancing factor 1 (LEF1) is a transcription factor mediating Wnt/β-catenin signaling. In this study, we analyzed the clinicopathologic significance of LEF1 expression in oral squamous cell carcinoma (OSCC). Methods: Expression levels of LEF1 in 135 cases of OSCC were determined by immunohistochemistry. The results were correlated with clinicopathologic parameters and patient outcome. Results: LEF1 was only occasionally detected in basal and parabasal cells of nontumorous squamous epithelium. Overexpression of LEF1 was observed in 33 of 135 OSCCs (24%). LEF1 was more frequently expressed in moderately to poorly differentiated cancer (p = 0.0035) and was associated with lymphovascular invasion (p = 0.0252). Overexpression of LEF1 was significantly associated with poor prognosis (p = 0.0176, hazard ratio = 1.96, 95% CI = 1.02–3.75). Multivariate analysis revealed LEF1expression and margin status to be the significant independent predictors for overall survival. Conclusion: Our study suggests LEF1 expression in OSCC may play an important role in tumor progression and can be served as a predictor of poor prognosis for patients with OSCC.